2021
DOI: 10.1007/s11845-021-02793-y
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 outbreak impact on emergency trauma visits and trauma surgery in a level 3 trauma center

Abstract: Background This study aims to compare emergency trauma visits' severity, emergency surgical needs, and characteristics between the pandemic and pre-pandemic periods. Methods This retrospective observational study was conducted in a tertiary training and research hospital between 1 and 30 April 2020 (pandemic group) and compared with the previous year's same dates (pre-pandemic group). Trauma patients aged 18 and over were included in the study. Emergency Severity Index (ESI) levels, trauma surgery needs, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…During the pandemic period, there was a significantly lower proportion of attendances for traffic accidents compared with the pre-pandemic period (n=426 vs n=658) in the same hospital 18 , largely coinciding with other studies 20,21,[30][31][32][33] . The restriction measures instituted by the City Hall, the closing of non-essential services, and the introduction of the home office system by several companies restricted the movement of vehicles and pedestrians in the city, which corroborates the result of this study.…”
Section: Silvasupporting
confidence: 84%
“…During the pandemic period, there was a significantly lower proportion of attendances for traffic accidents compared with the pre-pandemic period (n=426 vs n=658) in the same hospital 18 , largely coinciding with other studies 20,21,[30][31][32][33] . The restriction measures instituted by the City Hall, the closing of non-essential services, and the introduction of the home office system by several companies restricted the movement of vehicles and pedestrians in the city, which corroborates the result of this study.…”
Section: Silvasupporting
confidence: 84%
“…Goksoy et al (15) conducted a study with surgical emergency patients and reported a 25% decrease in admissions. Ilhan et al (7) showed a 60% reduction in adult trauma patients in their study. Also, Pintado et al ( 16) found an 80% decrease in orthopedic trauma applications in their study conducted at a first-level trauma center.…”
Section: Discussionmentioning
confidence: 80%
“…However, the number of DAMA adult trauma patients nearly doubled (94.7%) despite a decrease in all adult trauma patient visits during the pandemic period compared to the previous period (4.1%). In the study we carried out in the same center in the early stages of the pandemic, we showed that the ED visits of trauma patients decreased [ 13 ]. One of the reasons why trauma patients leave our hospital, which is a level 1 trauma center, before their treatment is completed, or do not want to come, may be that our ED accepts COVID-19 patients.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19, the pandemic of the century, has profoundly affected the habits of patients as well as the entire health system [ [11] , [12] , [13] ]. This includes ED visits, care and treatment of patients [ [11] , [12] , [13] ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation